Analisis Pegaruh Stres Kerja, Beban Kerja Dengan Kelelahan Kerja Terhadap Produktifitas Kerja Karyawan PT. Eastern Pearl Flour Mills Makassar Tahun 2020 - Usmawati; Syamsiar S Russeng; Haeruddin (Program Pascasarjana Universitas Muslim Indonesia, 2021)
Background: Accidents, injuries or occupational diseases cause many deaths each year. PT. Eastern Pearl Plour Milss Makassar is one of the wheat management industries in the form of flour products and a wheat milling capacity of 2800 tons per day which produces quality industrial flour. Quality results certainly cannot be separated from the role of employees in the production process. Employees are generally given tasks that are proportional to their fields, but sometimes with targets that must be achieved, as well as the presence of internal burdens on workers, it can be a problem that has the potential to cause stress and workload. On this basis the researcher intends to examine the effect of work stress and workload on work productivity with work fatigue as an intervening variable for employees of PT. Eastern Pearl Flour Mills Makassar. Methods: explanatory research used path analysis. With a total sample of 89 workers. Path analysis is carried out to analyze the inherent causal relationship between variables compiled using path coefficients as a measure of value in determining the magnitude of the influence of exogenous (independent) variables on endogenous (dependent) variables. SPSS 20.0 was used for the analysis of this study. Results: The results showed that there was a significant direct (-0.228) and indirect (-0.258) effect between job stress on work fatigue (p <0.05) through work fatigue on production employees of PT. Eastern Pearl Flour Mills Makassar City in 2020. Also, there was a direct effect (-0.315) and no significant indirect effect (-0.193) between workload on work productivity (p <0.05) through work fatigue on production employees of PT. Eastern Pearl Flour Mills in Makassar City in 2020. Conclusion: Conclusion of this study Work stress and workload had a direct effect on work productivity through work fatigue. Job stress had a significant indirect effect, but workload had not a significant indirect effect on work productivity through work fatigue.